A method for assessing support schemes promoting flexibility at district energy plants. (1st September 2018) - Andersen, Anders N.; Østergaard, Poul Alberg
Highlights: District energy plants may become major actors in integrating wind and solar power. Often electricity prices do not create sufficient feasibility for needed investments. Support should be minimized while ensuring adequate installed capacity at plants. Method for determine the production and store capacities support schemes will promote. The method used shows a premium scheme promotes more flexibility than a FIT scheme. Abstract: Flexible District Energy plants providing heating and cooling to cities have an important role in the transition to a renewable energy system. They may become major actors in integrating wind and solar power, when equipped with a combination of combined heat and power units, heat consuming absorption chillers, heat pumps producing both heating and cooling and large thermal energy stores. However, often electricity prices do not create sufficient feasibility for these to be installed thus calling for support schemes. The societal resources dedicated to support should be minimised while ensuring the establishment of an adequate amount and right ratio between these units. This paper presents a method for determining the capacities different support schemes will promote as a function of dedicated resources. The method is used in a comparison of two support schemes promoting combined heat and power; a premium on top of hourly wholesale electricity prices and a fixed Feed in Tariff. The comparison shows that the premium scheme requires a little less total support than the Feed In Tariff scheme for promoting a given amount of electrical capacity, but promotes a five-times larger thermal energy store capacity, thereby promoting substantially increased flexibility for integrating intermittent power production.